RIESGOS LABORALES DE LOS DOCENTES Y LA APLICACIÓN DE FACTORES ERGONOMETRICOS AMBIENTALES DURANTE SU PERMANENCIA EN EL COLEGIO TECNICO FISCAL Dr. JOSE MARIA VELASCO IBARRA DEL CANTON BUENA FE PROVINCIA DE LOS RIOS. - Hallo Ortiz, María Targelia (2014)
This research aims to know the current situation prevailing in educational institutions, regarding the ergonomic conditions of jobs. For this purpose technical attorney Dr. José Maria Velasco Ibarra of the Canton good faith province of the Ríos, were taken as case study school especially for the facilities provided by the institution. Amazing growth in the use of different teaching techniques in recent times has produced a special group of related ergonomic dilemmas exclusively with the teaching occupational hazard, they present a range of disorders to health, requiring of continue them to raise awareness to campus authorities heed the recommendations that exist so that workers develop their activities in a comfortable working environment and protecting their health. The objective of this research is to identify and assess risk factors ergonomic, which are impacting on teaching job performance. The study focused mainly on the evaluation of the following points: sound, lighting, temperature, dimensions of the uneasiness expressed by the respondent staff jobs. Once identified and evaluated the risk factors in a sample of 3 Directors, 76 teachers and 436 students, resulted in furniture (tables and chairs and work) stood out as one of the points poorer, not having the necessary minimum measures recommended in the literature, as well as the deterioration in which areit comes to the light atmosphere, found that light sources are not properly aimed, in some jobs light is insufficient, while for others, they feel discomfort by undesirable glare, noise that enters from the outside, the voice of the teacher who elopes by some classroom windows are very large as well same lack of training on risk factors ergonomic and the absence of a Safety Commission e Hygiene monitoring acts and unsafe conditions in each of the jobs is clear. As a result of this work were presented recommendations and preventive actions that must be followed in the future, without losing sight that minimum which are the risks faced by a teacher, regularly must be evaluated in order to minimize their effects. Keywords: ergonomic environment, factors of occupational hazard, conferences and insecure reality.